Symbiocene as an Effort to Build Ecological Balance In Danny Boyle's The Beach (2000) - Masnia Rahayu (TEKNOSASTIK, 2023)
AbstractThe development of tourism today poses a significant problem in terms of environmental damage. The exploitation of tourism has had a negative impact on natural resources and the environment, especially in tropical countries such as Thailand. Although many beaches have become part of a highly protected national park, many tourists and divers still have access to some of these locations. The Beach (2000) is a film that explores the relationship between humans and nature. In The Beach, the main characters in the film are tourists or foreign backpackers who have ambivalence about treating nature. By examining the film The Beach (2000) by Danny Boyle, the purpose of this study is to identify the role of nature in building ecological balance through the Symbiocene ideology. This study uses a qualitative method with narrative theory and cinematography by Boggs and Petrie (2008) in analyze the structure of the text and then using Albrecht's ecocritical approach (2019) in analyze the ideology of the text that focuses on the concept of human and natural relations. In the film The Beach (2000), nature can be positioned as an object or subject. The positioning of nature reflects a critique of anthropocentrism because humans are faced with two choices: to be the preserver or the destroyer. One of the roles of nature in building ecological awareness is building symbiotic bonds through conservation efforts and building insight into environmental care. Green politics in films can also refer to the ecotourism movement devoted to travelers.Keywords: symbiocene, ecological balance, backpackers, green politics, ecotourism.